COVID-19 or systemic lupus erythematosus: Attention to similarity - Erden Abdulsamet; Karakaş Özlem; Ulusoy Bahar Özdemir; Gemcioğlu Emin; İzdeş Seval; Güner Rahmet; Yarkan Handan; Erden Fatma; Omma Ahmet; Küçükşahin Orhan (Romanian Journal of Laboratory Medicine)
Arthralgia, myalgia, acute interstitial pneumonia-like presentation, venous thromboembolism, cytopenia, secondary hemophagocytic lymphohistiocytosis and cytokine storm are the clinical and laboratory findings associated with Coronavirus disease (COVID-19), which may mimic rheumatic syndromes. Systemic lupus erythematosus (SLE) is a highly heterogeneous disease, and various clinical features can be seen in affected individuals. Differentiated diagnoses are quite broad in SLE. We present six patients with systemic lupus erythematosus and/ or antiphospholipid syndrome mimicking COVID-19 pneumonia.